Study on the Effect of Breeds on Physiochemical Parameters of Goat Milk at National Goat Research Program, Bandipur Tanahun Nepal - Dahal, Maheshwar; Kadel, Raju; Ghimire, Shivahari; Acharya, Buddhi Ram (Nepalese Journal of Agricultural Sciences, 2026)
This study analyzed breed-specific variations in milk composition among pure Saanen, pure Boer, and pure Khari goats at National Goat Research Program in Bandipur, Tanahun between March and May, 2018. Using a milk analyzer, we evaluated 96 Saanen, 12 Boer, and 12 Khari milk samples for protein, fat, SNF, lactose, and freezing point. Statistical analysis was performed using SPSS software with mean comparisons at a 0.01 significance level. The results revealed no significant differences (p>0.01) among the breeds for protein, lactose, SNF, and freezing point values. However, pure Boer goats showed significantly higher fat content (7.96±0.48%) compared to both Saanen and Khari breeds (p<0.01), while no significant difference was observed in fat level between Saanen and Khari goat milk. Despite Boer goats having the highest fat percentage, theirlowmilk yield makesthemlesssuitable for dairy product manufacturing, particularly for cheese production. The comparative analysis demonstrated that Saanen goats possess superior milk production characteristics compared to both Khari and Boer breeds. Saanen is recommended as the most appropriate breed for commercial dairy processing in Nepal due to its balanced milk composition and better production performance.